Analysis of spectroscopic diffuse reflectance plots for different skin conditions. Issue 5 (2010) - Prince Prince, Shanthi Shanthi; Malarvizhi Malarvizhi, S. S.
Abstract : Optical means of characterizing tissues have gained importance due to its noninvasive nature. Spectral characteristics of the components provide useful information to identify the components, because different chromophores have different spectroscopic responses to electromagnetic waves of a certain energy band. The purpose of this study is to determine whether visible/near-infrared diffuse reflectance spectroscopy can be used to non-invasively characterize skin diseases in vivo . An optical fiber spectrometer is set up for obtaining diffuse reflectance spectra. The method involves exposure of skin surface to white light produced by an incandescent source. The back scattered photons emerging from various layers of tissue are detected by spectrometer resulting in diffuse reflectance spectra. For the present study different skin conditions like – warts, vitiligo, thrombus (due to injury) and angioma are chosen. The spectral data obtained from the scan are plotted and compared. More or less, the shapes of the spectral curves for various skin conditions resemble. In order to characterize and differentiate different diseased state spectral analysis based on Ratio analysis, Student's t -tests and difference plot are carried out. Based on the analysis the relative spectral intensity changes are quantified and the spectral shape changes are enhanced and more easily visualized on the spectral curves, thus assisting in differentiating the normal tissue from the one affected by disease.